Different responses to joint exposure to cadmium and zinc depends on the sex in Populus cathayana - Li, Xiaoyuan; Yang, Zaijun; Li, Yongcheng; Zhao, Hongxia (Ecotoxicology and environmental safety, 2022)
The alarming increase in soil contamination by heavy metals, such as cadmium and zinc demands immediate attention. The dioecious tree Populus cathayana, a phytoremediation plant, plays an important role in rehabilitating heavy metal contaminated areas. In this study, male and female P. cathayana plants were treated with Cd (20 mg kg−1) and different levels of Zn (25, 50, or 100 mg kg−1) to study their physiological responses. The results showed that Cd exposure alone caused stress by inhibiting the growth of both male and female plants. In both males and females, photosynthesis and antioxidant enzymes activities decreased substantially under Cd stress alone. Cd was largely located in the roots, but Zn was present in the shoots of both sexes. Zn supplementation considerably increased the photosynthetic rate from 14.62 % to 60.45 % and also enhanced the antioxidant enzymes activities from 24.11 % to 86.21 %. Zn treatment decreased the translocation ability of Cd compared to the Cd-only treatment, alleviating Cd toxicity. In addition, when sufficient Zn was made available, males showed a high degree of Cd accumulation, low root-to-shoot translocation, elevated antioxidant defense abilities, and an increased photosynthetic rate, while females were less responsive to Cd stress than males. Thus, combined exposure to Cd and Zn caused differential responses in plant growth and physiological processes between males and females P. cathayana. Male plants exhibit better Cd tolerance and accumulation capacity under optimum Zn supplementation. This study increases the fundamental knowledge regarding P. cathayana plants, which can be applied to enhance their remediation capacity in Cd-contaminated soils. [Display omitted] •Zn supplementation inhibited the Cd translocation from root to shoot.•Optimum Zn supplementation detoxified Cd by enhancing antioxidant defense and photosynthesis.•Male plants had better Cd tolerance than female plants.